Generality of the practical functional assessment and skill‐based treatment among individuals with autism and mental health disorders. (10th November 2020) - Coffey, Amanda L.; Shawler, Lesley A.; Jessel, Joshua; Bain, Taylor; Nye, Maggie; Dorsey, Michael F.
Abstract: A practical functional assessment format was recently developed that informed a skill‐based treatment for the problem behavior of children diagnosed with autism spectrum disorder. Since its inception there have been multiple replications of the procedures; however, the comprehensive model has rarely been applied to populations with more complex comorbid disorders and severe problem behavior such as those diagnosed with anxiety or depression. We conducted the current study to systematically replicate the entire practical functional assessment and skill‐based treatment model with two participants diagnosed with multiple mental health disorders admitted to a severe behavior outpatient unit. The practical functional assessment identified reinforcers that were provided contingent on increasingly complex forms of communication. Problem behavior remained low for both participants after reinforcement was thinned by increasing a response requirement of completing difficult tasks. Furthermore, the results were socially validated by the parents and teachers and the treatment was extended to the home setting.